Workers' knowledge in the ''knowledge society'': voices from the South. (1st July 2007) - Sujata Gothoskar
Abstract : Drawing on first-hand interviews with call centre workers in Mumbai, participant observation and a variety of secondary sources, including email forum contributions by call centre workers, this paper takes a critical look at the concept of the ''knowledge economy'' from the perspective of those who work in it. In particular, it questions the extent to which ''knowledge workers'' have access to the knowledge that underlies the work that they do and points to the ways in which this knowledge is eroded as value chains are extended. It also looks at these workers'' stakes in their skills and work, and concludes by pointing to a series of contradictions that are raised for Indian society by the rapid development of the knowledge economy there.